Editorial - Hayes, Grahame (PINS-Psychology in Society, 2025)
This issue of Psychology in society focuses on the psychology of repression. There might be some surprise from our readers about our carrying these articles when it seems that the "season of repression" is over since the F W de Klerk speech in early February this year. We need to remind ourselves that there have been no changes in security legislation and the current State of Emergency is still in operation. Furthermore, there are well over 100 people being held in detention under the Emergency Regulations, and a handful of Internal Security Act detainees. While it is true that the State has eased up on its use of formal repression, it is equally true that a complex web of repression - both formal and informal - still exists in South Africa. It is the wider implications of life under repression that the two articles by Adrian Perkel, and Shirley Spitz, Ruth Eastwood and Paul Verryn explore as they uncover some of the psychological hardships experienced by people in their struggles against oppression and exploitation.